Engaging “unusual suspects” in climate action: cultural affordances for diverse competences and improvised identities - Heiskanen, Eva (Frontiers in Sustainability, 2023)
The demonstrated urgency of the climate crisis would require mobilization by a larger and more diverse set of participants than those usually recognized as environmental activists. Hence this article asks: (1) What conditions enable unlikely participants (such as men working in manual occupations) to engage in and identify with a climate movement? And (2) what is it about the relationship between participants’ biographies, the practices of the climate movement and the interaction between them that allows – or affords – such identification to occur? I draw on an approach to identity formation as situated practice, i.e., as occurring in situations where social relations are enacted while drawing on the individual experience and shared understandings that participants bring to the situation. Based on fieldwork in Finnish municipalities that have committed to climate neutrality, I find that the conditions for engagement depend on socio-cultural affordances for engaging in climate action, which (1) accept and welcome participants’ life histories and lifestyles (2) build on and respect participants’ competences and multiple forms of expertise, (3) engage participants in practices that are familiar enough not to produce anxiety but stimulating enough to be fun, and (4) produce small but visible achievements that are acknowledged as such by both participants and onlookers. The current study contributes to previous research arguing for a more populist approach to climate policy by emphasizing existing competences and embodied practices as an avenue for engagement in climate action.